FACTORS DETERMINING HIGH PERFORMANCE ORGANIZATIONS WITHIN SMALL-SCALE PLASTIC COMPONENTS MANUFACTURING INDUSTRY IN INDIA - Jayaraj, Balaji (International Journal of Psychosocial Rehabilitation, 2020)
The world economic forum in the very recent global competitiveness report found that India is ranked as 39th out of 138 countries globally. Having the “population of 1292.7 (Millions), GDP 2090.7 (US$ billions), GDP per capita 1617.3(US$), GDP (PPP) % World GDP 7.02”. It is understood from the global competitiveness report that during the year 2012-2013 India was ranked 59th out of 144 countries and from then India has improved their performance and currently in 38th rank in 138 countries globally [1].